RELATIONSHIPS OF PHYSICAL FITNESS TEST RESULTS AND PLAYER PERFORMANCE INDICATORS IN NATIONAL-LEVEL ICE HOCKEY PLAYERS - Stanula, Arkadiusz Jarosław; Roczniok, Robert Krzysztof; Gabrys, Tomasz Tytus; Szmatlan-Gabrys, Urszula Barbara; Ozimek, Mariusz Jacek (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of the study is to identify the relationships of the results of the physiological and anthropometric tests and special on-ice fitness tests with individual player performance indicators during matches of the Poland men's national ice hockey team played during the U18 Ice Hockey World Championship. A total of 20 hockey players (forwards, n=12 and defensemen, n=8) of the Poland men's national ice hockey team were included in this study. All participants were performed a battery tests including maximal aerobic capacity, Wingate test, Repeated-Skate Sprint test and vertical jump test. Pearson correlations were used to examine any differences in all measures and +/– score. Only the fatigue index calculated from the repeated-skate sprint test was significantly correlated with absolute +/– score (r=0.47, p<0.05). The result of the aerobic capacity test, expressed by means of the oxygen intake value (V̇O2max), despite being statistically insignificant, reached the value of r=0.42. The results of this study suggest that game performance as indicated by the +/– score can be predicted by the fatigue index calculated from the repeated-skate sprint test.